ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN PELAKU USAHA PAKAIAN DI PASAR RAYA MOJOSARI, KECAMATAN MOJOSARI, KABUPATEN MOJOKERTO - Putri Citra Devi; Arga Christian Sitohang (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to analyze the factors that influence the income of clothing business operators at Pasar Raya Mojosari, Mojosari District, Mojokerto Regency. The research employs a quantitative approach with multiple linear regression analysis using SPSS version 25. The data used consist of primary data obtained from questionnaires distributed to clothing business operators, and secondary data sourced from the Pasar Raya Mojosari office. The sampling technique used is saturated sampling, involving 38 respondents. The results show that the variables of product quality (X1) and price (X2) have a negative and significant effect on business income (Y). In contrast, the demand variable (X3) has a positive and significant effect on income (Y). These findings suggest that product quality, pricing strategies, and market demand play an essential role in determining the income levels of clothing entrepreneurs at Pasar Raya Mojosari. It is hoped that this research can provide useful insights and input for clothing business operators to make better decisions, particularly regarding pricing and product quality, to enhance their business performance.